دور الهاشميين في إعمار المقدسات الإسلامية (المسجد الأقصى وقبة الصخرة) من وجهة نظر أعضاء هيئة التدريس في مساق التربية الوطنية والسبل المقترحة لتفعيل هذا الدور (1924م - 2017م) - الكساسبة، ميساء الشيخ محمدعلي (جامعة القدس المفتوحة, 2018)
تهدف هذه الدراسة إلى التعرف على دور الهاشميين في إعمار المقدسات الإسلامية) المسجد الأقصى، وقبة الصخرة (في مساق التربية الوطنية من وجهة نظر أعضاء هيئة التدريس. واستخدمت الباحثة المنهج النوعي عن طريق المقابلة، حيث تمّ اختيار أفراد الدراسة بطريقة قصدية ممن لديهم اطلاع على مساقات التربية الوطنية والإعمار الهاشمي، وّبلغ عددهم (15) عّضوا من أعضاء هيئة التدريس في الجامعات الأردنية (آل البيت، الأردنية، اليرموك). وبينت نتائج الدراسة تأكيد أعضاء هيئة التدريس في الجامعات الأردنية على دور الهاشميين الواضح في عملية إعمار المسجد الأقصى وقبة الصخرة، وأن من أهم السبل والتوصيات المقترحة لتفعيل دور الهاشميين في الإعمار الهاشمي للمقدسات الإسلامية (المسجد الأقصى، وقبة الصخرة) في مساق التربية الوطنية من وجهة نظر أعضاء هيئة التدريس التركيز على الدور الهاشمي المميز في قيادة الأمة وإضافة مقدمة عن دور الهاشميين دينيا وتاريخيا. وأوصت الباحثة بضرورة أن يدرس موضوع الوصاية الهاشمية على مدينة القدس ومقدساتها الإسلامية من قبل خبراء متخصصين في دراسة تاريخ المنطقة، وأن تركز المادة على تذكير الجيل القادم بتاريخهم المجيد والدعوة إلى يقظتهم.
This study aims to identify the role of the Hashemites in the reconstruction of Islamic Holy places (al-Aqsa Mosque and the Dome of the Rock) in the course of National Education from the point of view of faculty members. The researcher used the qualitative approach via interviews. The research participants were chosen deliberately from those enrolled in the National Education and the Hashemite Reconstruction courses. The number of faculty members in Jordanian universities (al-Bayt, Jordan University and Yarmouk University) is 15. The study confirmed the importance of the Hashemite custodianship role of al-Aqsa Mosque and the Dome of the Rock, as part of the curriculum of the course of National Education from the point of view of the members of the faculty. The results of the study affirmed the belief of the faculties’ members in the abovementioned Jordanian universities the role of the Hashemite’s reconstructions of al-Aqsa Mosque and the Dome of the Rock. It also stressed that one of the most important ways and recommendations proposed to activate the custodianship role of the Hashemites on the Islamic Holy sites (al-Aqsa Mosque and the Dome of the Rock) is to focus on the distinguished Hashemite’s role in leading the nation and to add an introduction on the religious and historical role of Hashemites within the course of National Education. The researcher recommended that the subject of the Hashemite tutelage over the City of Jerusalem and its Islamic Holy sites should be studied by experts specialized in studying the history of the region. The course should focus on reminding the next generation of their glorious history and calling for their vigilance.
Keywords: المسجد الأقصى -- قبة الصخرة -- المقدسات الإسلامية -- الهاشميين -- التربية الوطنية -- أعضاء هيئة التدريس -- الجامعات الأردنية